Tom and the tree house - "Lingard, Joan" (Hodder Childrens books: London, 1998)
Tom is adopted. He has always known about it, but the arrival of a new baby makes him feel less special any more. He retreats from his parents in his hideaway tree house. Now they have to show him that they want and love him, and he has to accept his new baby sister.
Keywords: Tree houses fiction